The Floating Signifier of “Radicalization”: Correctional Officers’ Perceptions of Prison Radicalization - Schultz, William J. (Criminal justice and behavior, 2021)
The number of people incarcerated for extremist actions has grown over the past decades. The resulting prospect of prison radicalization has contributed to widespread risk responsibilitization among prison staff. Low-level correctional officers now perceive themselves as being directly responsible for detecting radicalization on their units. Consequently, radicalization has become a meaningful topic for prison staff, one which shapes their daily actions and perceptions. However, officers’ understandings of radicalization may not conform with accepted definitions. Through 131 semistructured interviews with Canadian correctional officers, we demonstrate how radicalization functions as a floating signifier in prison, influencing officer thought and behavior in meaningful ways while eluding easy definition. Officers redefine radicalization to fit interpretive frames around religion and race, gang membership, and mental health, irrespective of whether stereotypical extremists exist in a given prison. We demonstrate how radicalization, when operating as a floating signifier, can significantly influence officers’ perceptions and front-line prison operations.